Factors Related to Dengue Hemorrhagic Fever (DHF) in Bontang Kuala Sub- district, North Bontang District - Shandy, Adelia Fitria; Badrah, Sitti; Sedionoto, Blego (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2023)
Dengue Hemorrhagic Fever is one of the leading public health problems in Indonesia. The number of DHF pain in Bontang Kuala Sub-district has increased over the past three years, namely 5 cases in 2019, 19 cases in 2020, and 33 cases in 2021. This study aims to determine several factors related to dengue disease in Bontang Kuala Sub-district, North Bontang District. This type of research used a cross-sectional study design. The population in this study was 1,791 households and a sample of 91 respondents. Samples were taken using the proportional random sampling method. The data analysis technique used a chi-square test with a degree of meaningfulness (p = 0.05). The results of this study showed that 68.1% of respondents had poor used goods management with (p = 0.000), 65.9% had good waste disposal facilities with (p = 0.164), 64.8% had a habit of hanging clothes less well with (p = 0.001) and 72.5% had a habit of using anti- mosquito lotion less well with (p = 0.002). This research advises people to make more frequent efforts to eradicate mosquito nests (PSN) coupled with avoiding the habit of hanging clothes and using mosquito-repellent lotions so that the transmission of DHF disease can be reduced.